Esterification of Free Fatty Acid with High Chain Alcohol for Biodiesel Production Using Semi-Batch Reactive Distillation - Mohammed, Wadood T.; Abdul Jabbar, Marwa F. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The esterification of oleic acid with 2-ethylhexanol in presence of sulfuric acid as homogeneous catalyst was investigated in this work to produce 2-ethylhexyl oleate (biodiesel) by using semi batch reactive distillation. The effect of reaction temperature (100 to 130°C), 2-ethylhexanol:oleic acid molar ratio (1:1 to 1:3) and catalysts concentration (0.2 to 1wt%) were studied. Higher conversion of 97% was achieved with operating conditions of reaction temperature of 130°C, molar ratio of free fatty acid to alcohol of 1:2 and catalyst concentration of 1wt%. A simulation was adopted from basic principles of the reactive distillation using MATLAB to describe the process. Good agreement was achieved.